The Language of Balinese Shadow Theater - Zurbuchen, Mary Sabine (Book collections on Project MUSE., 2014)
Bali's shadow puppet theater, like others in Southeast Asia, is a complex tradition with many conventions that puzzle Western observers. Mary Zurbuchen demonstrates how the linguistic codes of this rich art form mediate between social groups, cultural influences, historical periods, and conceptual schemes. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original text.